Emergence of apospory and bypass of meiosis via apomixis after sexual hybridisation and polyploidisation. Issue 4 (31st July 2014) - Hojsgaard, Diego; Greilhuber, Johann; Pellino, Marco; Paun, Ovidiu; Sharbel, Timothy F.; Hörandl, Elvira
Summary: Hybridisation and polyploidy are major forces contributing to plant speciation. Homoploid (2x) and heteroploid (3x) hybrids, however, represent critical stages for evolution due to disturbed meiosis and reduced fertility. Apomixis – asexual reproduction via seeds – can overcome hybrid sterility, but requires several concerted alterations of developmental pathways to result in functional seed formation. Here, we analyse the reproductive behaviours of homo‐ and heteroploid synthetic hybrids from crosses between sexual diploid and tetraploid Ranunculus auricomus species to test the hypothesis that developmental asynchrony in hybrids triggers the shift to apomictic reproduction. Evaluation of male and female gametophyte development, viability and functionality of gametes shows developmental asynchrony, whereas seed set and germinability indicate reduced fitness in synthetic hybrids compared to sexual parents. We present the first experimental evidence for spontaneous apospory in most hybrids as an alternative pathway to meiosis, and the appearance of functional apomictic seeds in triploids. Bypassing meiosis permits these triploid genotypes to form viable seed and new polyploid progeny. Asynchronous development causes reduced sexual seed set and emergence of apospory in synthetic Ranunculus hybrids. Apomixis is functional in triploids and associated with drastic meiotic abnormalities. Selection acts to stabilise developmental patterns and to tolerate endosperm dosage balance shifts which facilitates successful seed set and establishment of apomictic lineages.